Monitoring the Filtration of Brackish Water Into Raw Water by the Reserve Osmosis Method - Basit, Abdul; Afriliana, Ida (Westscience Press, 2024)
The need for raw water is still a serious problem for coastal communities, where groundwater obtained by coastal communities cannot be categorized as suitable for use, because the water tends to be brackish. Clean water that is suitable for consumption is not only clear, odorless, and tasteless, but must also meet health requirements. The urgency of the condition in the coastal area is that with the development of housing located on the coast, the need for clean water is very important for people living on the coast. The purpose of this study is to implement appropriate technology in the coastal area of the north coast with the hope of providing raw or usable water for the people of the north coast, especially for the people in the coastal area of Tegal City, Central Java. The appropriate technology that will be applied is to monitor the results of an internet-of-things based filtration system by reading the TDS and PH sensor values. The TDS sensor can detect a decrease in moisture content with an average decrease in PPM value of around 321 and salinity or salt levels, which is an average decrease of about 8.63%, while the PH sensor detects an increase in the sample, which is an average of 1.8 with a water filling speed of 9.03 L/min. Thus, the previously brackish water condition can be used as an effort to overcome the raw water crisis in coastal communities with the reserve osmosis filtration method.